PENGEMBANGAN KURIKULUM DENGAN MEMANFAATKAN TEKNOLOGI INFORMASI DAN KUMUNIKASI, SUATU GAGASAN - nFn Sutjipto (Kwangsan: Jurnal Teknologi Pendidikan, 2016)
The purpose of this paper was to examine the repertoire of ideas for curriculum development by utilizing information and communication technology in order to provide a breakthrough on the dynamics and complexity of curriculum development practices. Results of the study showed. First, the management of the curriculum development process that includes activities to share ideas, argument, contributedscientific papers, give feedback, provide feedback, the rationality of the policy decision makers, data processing, how the curriculum management, and results of develop ment can utilize information and communication technologies. Second, to take advantage of information technology and communication in curriculum development has some added value, such as easy in terms of faster information obtained, the cost in the sense that it does not require huge resources, broad reach in the sense that everyone can get involved, efficient and effective way to share, and provide a forum of freedom of speech which is at once loose the bonds of values or certain cultural norms. Third, the idea of developing a curriculum by utilizing information and communication technology as well as encouraging developers literate not only technology, but also able to understand, perceive, and apply power to the significance of the technology. Fourth, curriculum development by utilizing information and communication technology is considered a breakthrough way of working in this digital era AbstrakTujuan dari penulisan ini adalah ingin mengkaji khasanah gagasan pengembangan kurikulum dengan memanfaat kan teknologi informasi dan komunikasi yang diharapkan dapat memberi terobosan mengenai dinamika dan kompleksitas praktik (praxis) pengembangan kurikulum. Hasil kajian menunjukkan. Pertama, pengelolaan proses pengembangan kurikulum yang mencakup aktivitas berbagi gagasan, adu argumen, berkontribusi karya tulis ilmiah, memberi tanggapan, memberi masukan, rasionalitas kebijakan pembuat keputusan, pengolahan data, cara kerja manajemen kurikulum, dan hasil dari pengembangan dapat mendayagunakan teknologi informasi dan komunikasi. Kedua, dengan memanfatkan teknologi informasi dan komunikasi dalam pengembangan kurikulum memiliki beberapa nilai tambah, seperti mudah dalam arti informasi lebih cepat diperoleh, murah dalam arti tidak memerlukan sumber daya yang besar, jangkauan luas dalam arti semua orang dapat terlibat, efisien dan efektif untuk berbagi, dan memberi wadah kebebasan berpendapat yang sekaligus lepas dari ikatan nilai-nilai atau norma budaya tertentu. Ketiga, gagasan pengembangan kurikulum dengan memanfaatkan teknologi informasi dan komunikasi sekaligus mendorong pengembang bukan hanya literate teknologi, tetapi juga mampu memahami, mempersepsi, dan mengaplikasikan arti penting daya guna teknologi. Keempat, pengembangan kurikulum dengan memanfaatkan teknologi informasi dan komunikasi dinilai merupakan terobosan cara kerja di era digital ini